Answer:
U = -5
Step-by-step explanation:
-8u = -7u + 5
-u = 5
u = -5
Answer:
8,670
Step-by-step explanation:
because if 102 dollars per plate you take 102x85 = 8,670
<span>C.
glacial melting<<<<<<<<<<<<<<<</span>
Answer:
![(s.t)(x) = 4x^2+24x^2\\(s-t)(x) = x+6-4x^2\\(s+t)(-3) = 39](https://tex.z-dn.net/?f=%28s.t%29%28x%29%20%3D%204x%5E2%2B24x%5E2%5C%5C%28s-t%29%28x%29%20%3D%20x%2B6-4x%5E2%5C%5C%28s%2Bt%29%28-3%29%20%3D%2039)
Step-by-step explanation:
Given functions are:
![s(x)= x+6\\t(x)= 4x^2](https://tex.z-dn.net/?f=s%28x%29%3D%20x%2B6%5C%5Ct%28x%29%3D%204x%5E2)
We have to find:
(s.t)(x) => this means we have to multiply the two functions to get the result.
So,
![(s.t)(x) = s(x)*t(x)\\= (x+6)(4x^2)\\=4x^2.x+4x^2.6\\=4x^3+24x^2](https://tex.z-dn.net/?f=%28s.t%29%28x%29%20%3D%20s%28x%29%2At%28x%29%5C%5C%3D%20%28x%2B6%29%284x%5E2%29%5C%5C%3D4x%5E2.x%2B4x%5E2.6%5C%5C%3D4x%5E3%2B24x%5E2)
Also we have to find
(s-t)(x) => we have to subtract function t from function s
![(s-t)(x) = s(x) - t(x)\\= (x+6) - (4x^2)\\=x+6-4x^2](https://tex.z-dn.net/?f=%28s-t%29%28x%29%20%3D%20s%28x%29%20-%20t%28x%29%5C%5C%3D%20%28x%2B6%29%20-%20%284x%5E2%29%5C%5C%3Dx%2B6-4x%5E2)
Also we have to find,
(s+t)(-3) => first we have to find sum of both functions and then put -3 in place of x
![(s+t)(x) = s(x)+t(x)\\= x+6+4x^2](https://tex.z-dn.net/?f=%28s%2Bt%29%28x%29%20%3D%20s%28x%29%2Bt%28x%29%5C%5C%3D%20x%2B6%2B4x%5E2)
Putting x = -3
![= -3+6+4(-3)^2\\=-3+6+4(9)\\=3+36\\=39](https://tex.z-dn.net/?f=%3D%20-3%2B6%2B4%28-3%29%5E2%5C%5C%3D-3%2B6%2B4%289%29%5C%5C%3D3%2B36%5C%5C%3D39)
Hence,
![(s.t)(x) = 4x^2+24x^2\\(s-t)(x) = x+6-4x^2\\(s+t)(-3) = 39](https://tex.z-dn.net/?f=%28s.t%29%28x%29%20%3D%204x%5E2%2B24x%5E2%5C%5C%28s-t%29%28x%29%20%3D%20x%2B6-4x%5E2%5C%5C%28s%2Bt%29%28-3%29%20%3D%2039)